Risk of malignant transformation and infections in congenital lung malformations in adults: a systematic review - Federica Pederiva; Paolo Dalena; Noemi Pasqua; Ilia Bresesti; Valeria Testa; Salvatore Zirpoli; Valerio Gentilino (European Respiratory Review, 2025)
Background Although there is agreement on surgically removing symptomatic congenital lung malformations (CLMs), the management of asymptomatic cases remains controversial. Some paediatric surgeons suggest conservative management for asymptomatic cases due to the low perceived risk of developing symptoms or malignancy. This study aimed to investigate the characteristics and management of adults with CLMs. Methods Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a systematic review was conducted to find studies reporting on adult patients (aged ≥15 years) with CLMs. Results Out of 12 908 studies reviewed from 1947 to 2024, 653 studies met the inclusion criteria, covering 980 patients. None of the patients had a prenatal diagnosis. The mean±sd age at surgery was 39.4±15.7 years (range 15–86). A total of 74.4% of adults with CLMs presented with symptoms, leading to the detection of CLM. Pneumonia was the most common symptom in congenital pulmonary airway malformation (CPAM) and intralobar sequestration, with over 30% of these patients experiencing recurrent respiratory infections. In 11.7% of adults, CLMs harboured tumours at the time of surgical removal, with CPAM associated with lung tumours in over 20% of cases. Conclusions Thoracic surgeons recommend surgical resection for all adult CLM patients, including asymptomatic cases, due to risks of infections and malignancy. Conservative management was considered only when surgery was not feasible